Konstruksi Opini Publik melalui Media Sosial: Studi Pendekatan Analisis Wacana Kritis Grup Facebook Lintas Kejadian Kota Jayapura pada Bulan Juni 2021 - M. Zaenul Muttaqin; Sriyono Sriyono (Politicos: Jurnal Politik Dan Pemerintahan, 2021)
Public opinion has a very strategic function. In a democratic country, public opinion has a dual functions. First, as a mechanism of democratic control. Second, public opinion has function as factors for finding political decisions that answered people's aspirations. The purpose of this study was to explore the Jayapura City Cross-Genesis Facebook group (LKKJ) as a cyberspace that forms public opinion as well as a virtual community. Type of this research is qualitative research. Data analyzed of this research are form of pictures and writings. The secondary data source comes from one of the social media platforms, named facebook group "Info Jayapura City Events (IKKJ)". Data analyzed used a critical discourse analysis approach with the model approach developed by Fairclough. The results of this study that, textual analysis (micro level) of the text structure of facebook group Cross Events in Jayapura City (LKKJ) as a communication transmission presents a form of communication reproduction as well as a discursive arena that places the public as the subject of discourse. Dimensions of discourse practice (meso level), at the level of praxis, the centralization of discourse according to Fairclough is in the production process, distribution and consumption of texts. Dimensions of social practice (macro layer), The LKKJ facebook group is one of the production spaces for visual culture. With the background that connects the journalictic substance to be built.